Do patients with von Willebrand disease exhibit higher blood loss and revision rates in hip and knee arthroplasty? A case‐control study. Issue 3 (11th March 2020) - Kocaoğlu, Hakan; Hennes, Fabian; Abdelaziz, Hussein; Sandiford, Nemandra A.; Gehrke, Thorsten; Citak, Mustafa
Abstract: Background: The aim of the study was to compare the perioperative blood loss, need for transfusion and one‐year revision rates in patients undergoing hip and knee arthroplasty who also have a diagnosis of von Willebrand disease (VWD) with a matched control group. Methods: A retrospective single‐centre case‐control study was conducted. Fifty‐eight patients with VWD and 116 controls (1:2 match) who were operated for primary or revision hip and knee arthroplasty at our hospital were included. Blood loss, haemoglobin (Hb)‐drop, need for blood transfusion, intraoperative complications and revision rates within one year were noted in all cases. Outcome measures for subgroups of the primary hip, primary knee, revision hip and revision knee procedures, were also analysed. Results: The mean perioperative Hb‐drop was 3.47 (±1.27) g/dL and blood loss was 293 (±97) ml for the VWD group while Hb‐drop was 2.85 (±1.21) g/dL and blood loss was 232 (±105) mL for the control group ( P < .001). There were no significant increased transfusion rates ( P = .264) and revision rates in the VWD group ( P = .634). Patients having primary hip surgery had significantly higher Hb‐drop (3.68 ± 1.25 g/dL vs 2.62 ± 1.19 g/dL; P = .003), higher blood loss (293 vs 203 mL; P = .002) and increased need for a transfusion (21% vs 2.6%; P = .038) compared to the controls. No outcome measure was found to be significantly different for primary and revision knee surgery. Conclusions: The results of this study suggest that patients with VWD undergoing primary or revision total hip and knee arthroplasty have higher levels of blood loss than the control cohort. Perioperative protective measures including meticulous surgical techniques should be considered.